A Preliminary Study on the Relationship between Death Anxiety, Spiritual Well-being and the Meaning of Life among Individuals Living in Klang Valley, Malaysia - Hoesni, Suzana Mohd (International Journal of Psychosocial Rehabilitation, 2020)
To investigate the relationship between death anxiety, spiritual well-being and the meaning of life among individuals from critically developed areas in Klang Valley, Malaysia. This is an exploratory research study. The study involved 309 participants who were selected using the cluster sampling method from 10 of the most critically developed locations in Klang Valley, Malaysia. Questionnaires were distributed to respondents who had stated their agreement to the informed consent. The questionnaires consisted of questions regarding personal background, death anxiety, spiritual well-being and the meaning of life. Completed questionnaires were then collected and analyzed. The results show that there is a small, negative and significant relationship between the dimensions of death anxiety (extinction) and spiritual well-being (existential) (rs=- 0.12**, p